Isolation, characterization and therapeutic evaluation of a new Acinetobacter virus Abgy202141 lysing Acinetobacter baumannii - Tian, Xun; Liu, Xiang; Zhou, Jianhong; Wang, Li; Wang, Qinrong; Qi, Xiaolan; Liu, Jiayu; Zhao, Dailin; Hsiang, Tom; Jiang, Yinhui (Frontiers in Microbiology, 2024)
Acinetobacter baumannii is an opportunistic pathogen that easily resists currently available antibiotics. Phages are considered alternative therapeutic agents to conventional antibiotics for the treatment of multidrug-resistant bacteria. We isolated an Acinetobacter virus Abgy202141 from underground sewage in a residential area of Guiyang City in China. Transmission electron microscopy (TEM) analysis showed that Acinetobacter virus Abgy202141 has an icosahedral head attached to a tail. This phage infects A. baumannii strain GY-4, and was found to have a short latent period of 5 min, and with a burst size of 189 particles per infected host cell. Additionally, Acinetobacter virus Abgy202141 remained stable at different concentrations of chloroform and varying pH levels and temperatures. Based on SDS-PAGE analysis, it contained 14 proteins with molecular weights ranging from 12 to 125 kDa. The double-strand (ds) DNA genome of Acinetobacter virus Abgy202141 consisted of 41,242 bp with a GC content of 39.4%. It contained 50 open reading frames (ORFs), of which 29 ORFs had identified functions, but no virulence-related genes, antibiotic-resistance genes, or tRNAs were found. Phylogenetic analysis indicated that Acinetobacter virus Abgy202141 was a new phage in the Friunavirus genus.Acinetobacter virus Abgy202141 also showed the ability to prevent A. baumannii infections in the Galleria mellonella in vivo model.